2015
DOI: 10.1007/s12010-015-1770-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Production of Heterotrophic Chlorella sp. from Hydrolysate Mixtures of Lipid-Extracted Microalgal Biomass Residues and Molasses

Abstract: This study investigated the feasibility of lipid production of Chlorella sp. from waste materials. Lipid-extracted microalgal biomass residues (LMBRs) and molasses were hydrolyzed, and their hydrolysates were analyzed. Five different hydrolysate mixture ratios (w/w) of LMBRs/molasses (1/0, 1/1, 1/4, 1/9, and 0/1) were used to cultivate Chlorella sp. The results showed that carbohydrate and protein were the two main compounds in the LMBRs, and carbohydrate was the main compound in the molasses. The highest biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
(41 reference statements)
0
7
0
1
Order By: Relevance
“…These results also show that cultivation strategies, such as fed‐batch cultures are necessary to obtain high cell density cultures and therefore high lipid productivities. A relatively high amount of microalgal cell mass (5.58 g L −1 ) and content of lipids (42%) was obtained in batch mode when Chlorella sp was cultivated using a mixture of hydrolyzed molasses and microalgal biomass residues (where the lipids were previously extracted) . This work demonstrated that Chlorella sp, can use mixed sugars and amino acids to accumulate lipids efficiently.…”
Section: Lipidsmentioning
confidence: 82%
See 1 more Smart Citation
“…These results also show that cultivation strategies, such as fed‐batch cultures are necessary to obtain high cell density cultures and therefore high lipid productivities. A relatively high amount of microalgal cell mass (5.58 g L −1 ) and content of lipids (42%) was obtained in batch mode when Chlorella sp was cultivated using a mixture of hydrolyzed molasses and microalgal biomass residues (where the lipids were previously extracted) . This work demonstrated that Chlorella sp, can use mixed sugars and amino acids to accumulate lipids efficiently.…”
Section: Lipidsmentioning
confidence: 82%
“…This work demonstrated that Chlorella sp, can use mixed sugars and amino acids to accumulate lipids efficiently. Chlorella vulgaris has also been studied to improve nutrient removal from wastewater mixed with waste glycerol from biodiesel production . In heterotrophic batch cultures with 10 g L −1 of glycerol, total ammonia and 95% of the nitrogen was removed from the wastewater used with a concomitant production of C. vulgaris cell mass and lipids (Table ).…”
Section: Lipidsmentioning
confidence: 99%
“…Apart from glucose, other substrates such as acetic acid, ethanol, and molasses can be used . However, promising results have also been obtained utilizing biological waste such as dairy waste as well as hydrolysates of microalgae after lipid extraction .…”
Section: Microalgae Production Systemsmentioning
confidence: 99%
“…For assessment of preeminent, eco‐friendly, and effective approach, it is prerequisite to expand the efficiency and develop economical approaches of biodiesel production from living organisms, let us say the most favorite one are microalgae (Kishore et al, ; Sajjadi, Chen, Raman, & Ibrahim, ). Friendly nature, higher yields per unit area, growing potentially in a variety of water and/or medium and yield more energy per unit weight related to other energy sources are the prevailing advantages of algae for biodiesel production (Abomohra et al, ; Leite, Paranjape, Abdelaziz, & Hallenbeck, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, glycerol, a by‐product yield through biodiesel production, was found to perform well by enhancing the biomass, lipid contents, and thus helping in drop biofuel cost (Paranjape, Leite, & Hallenbeck, ; Zhang et al, ). It is attention grabbing to investigate the magnitude of HT and MT cultivation (using glycerol) on growth rate, biomass, and lipid content upon wild isolated native species collected from Cholistan desert as this could potentially be used as a strategy to increase biofuel productivity in an energy deficient zone (Alam et al, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%